Pseudomesotheliomatous carcinoma of the lung - Vuković Jelena; Plavec Goran; Aćimović Slobodan; Jović Milena; Stojsavljević Marko; Trimčev Jovana; Nikolajević Sanja; Skuletić Vesna; Lončarević Olivera; Živković Vladan; Zolotarevska Lidija; Cerović Snežana (Vojnosanitetski Pregled)
Introduction. Pseudomesotheliomatous lung carcinoma is a special, rare entity characterized by large pleural growth and minor invasion of lung tissue. Clinically, radiologically, macroscopically and even histologically this tumor can be misdiagnosed as malignant pleural carcinoma. Case report. We represent a 64-year-old male patient, former smoker. Due to difficulties in the form of dry cough, feeling of dis-comfort and pain in the right hemithorax, fatigue, heavy breathing, sweating, fever up to 39.6°C the patient was treated as with combined antibiotic therapy (macrolides, cephalosporins and penicillin), but without improving of his condition. Chest radiography showed a shadow of pleural effusion by the height of the front end of the third right rib. Chest MSCT showed the extremely thickened pleura apically and to the posterior along the upper right lobe in addition to existence of massive pleural effusion. Subpleural condensation of parenchyma ranging about 30 mm was described in the upper right lobe. Cytological analysis of the pleural effusion showed the presence of malignant cells impossible to differentiate whether they were metastasis of adenocarcinoma or malignant pleural mesothelioma. By histochemical and immunohistohemical analyses of a pleural sample, pseudomesotheliomataus lung adenocarcinoma was diagnosed. Conclusion. Pseudomesotheliomataus carcinoma of the lungs can be a diagnostic problem. Its diagnosis is based on recognition of histopathological characteristics which enable its discernment from the epithelial variant of malignant pleural mesothelioma.